Design and development of control system for Internet-based telerobotics - Zakaria, M. F.; Amin, S. H. M.; Mamat, R. (ieee, 2000)

(untitled)
This paper presents ways to design the basic development of control system for a prototype Internet-based telerobotics using a fixed type robot by considering the philosophy of design. There are three issues should be considered before telerobot control system is developed. They are operation safety and error issues, response time issues and continuous control issues. After that, the telerobotics system is developed depend on the design approach, system architecture and control scheme. In this project, robot control system has developed by using C++ programming language, whereas Java programming language has been used to program the camera image feedback. These systems are combined together by using HTML technology. Finally, this telerobot system has been successful done and allowed the user to manipulate a robotics arm, through the Web browser interface, to perform simple tasks such as moving small plate of steel